Penerapan Problem-Based Learning Berbantuan Wordwall dalam Mencapai Ketuntasan Motivasi Belajar dan Pemahaman Konsep SPLDV - Komang Winanti Dewi; Sanapiah; Eliska Juliangkary (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2026)
This study aimed to analyze the implementation of Wordwall-assisted Problem-Based Learning (PBL) in achieving mastery of learning motivation and mathematical conceptual understanding of Systems of Linear Equations in Two Variables. The study employed Classroom Action Research based on the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection. It was conducted in one cycle comprising four meetings and involved 23 Grade VIII-A students of SMP Negeri 2 Tanjung. Data were collected through a learning motivation questionnaire, a mathematical conceptual understanding test, teacher and student activity observation sheets, and documentation. All learning materials and research instruments underwent expert validation. The data were analyzed using quantitative and qualitative descriptive techniques. The results showed that 19 students, or 83%, achieved the mastery criterion for learning motivation, with an average percentage of 81%, categorized as very high. Regarding mathematical conceptual understanding, 19 students, or 83%, achieved the minimum score of 75, with a class average of 84.1. Teacher activity reached 99% and was categorized as very good, while student activity reached 89% and was categorized as very active. All results exceeded the predetermined classical mastery criterion of 80%; therefore, the action was concluded in Cycle I. Wordwall-assisted PBL thus supported the achievement of mastery in learning motivation and conceptual understanding, although several students still required guidance in constructing mathematical models and solving problems systematically